2004
DOI: 10.1097/01.alc.0000108661.41560.bf
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Binge Alcohol Exposure on Bone Resorption and Biomechanical and Structural Properties are Offset by Concurrent Bisphosphonate Treatment

Abstract: Background-Chronic alcohol consumption reduces bone mass and strength, increasing fracture risk for alcohol abusers. Mechanisms underlying this vulnerability involve modulation of bone remodeling. Direct effects of alcohol on bone formation have been documented; those on bone resorption are less well studied. Skeletal effects of exposure to high blood alcohol concentrations (BAC's) attained during binge drinking have not been studied. We examined the effects of repeated binge-like alcohol treatment on bone res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 43 publications
4
53
1
3
Order By: Relevance
“…The normative consumption level used in alcohol research studies is more than 4 drinks during a single occasion (female) or more than 5 drinks during a single occasion (male) resulting in acute intoxication [1]. Experimentally this can be mimicked by repeated alcohol injections separated by periods of no alcohol administration [2]. This investigation is based on those previous studies in which we demonstrated that the bisphosphonates alendronate and risedronate effectively prevent cancellous bone loss and reduced bone strength in intact male and female rats after chronic consumption of alcohol and after binge alcohol treatments [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The normative consumption level used in alcohol research studies is more than 4 drinks during a single occasion (female) or more than 5 drinks during a single occasion (male) resulting in acute intoxication [1]. Experimentally this can be mimicked by repeated alcohol injections separated by periods of no alcohol administration [2]. This investigation is based on those previous studies in which we demonstrated that the bisphosphonates alendronate and risedronate effectively prevent cancellous bone loss and reduced bone strength in intact male and female rats after chronic consumption of alcohol and after binge alcohol treatments [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally this can be mimicked by repeated alcohol injections separated by periods of no alcohol administration [2]. This investigation is based on those previous studies in which we demonstrated that the bisphosphonates alendronate and risedronate effectively prevent cancellous bone loss and reduced bone strength in intact male and female rats after chronic consumption of alcohol and after binge alcohol treatments [2,3]. In addition, our previous studies demonstrated that parathyroid hormone given intermittently has a similar preventive effect on the loss of cancellous bone mineral density and bone strength after binge alcohol treatment [4].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, most alcoholics exhibit radiographic evidence of osteopenia (Bilke et al, 1985), leading to a hypothesis that reduced osteoblast activity resulting in underfilling of resorptive lacunae is primary responsible for alcohol-induced bone loss (Turner et al, 2001). Ethanol has been shown to increase bone resorption (Callaci et al, 2004) and to decrease trabecular bone volume (Rico et al, 1987). Additionally, administration of ethanol to healthy volunteers results in an acute decrease in serum osteocalcin levels (Rico et al, 1987, Nielsen et al, 1990.…”
Section: Discussionmentioning
confidence: 99%
“…Acredita-se que o consumo crônico de etanol conduz à perda óssea sistemática por redução na ingestão de nutrientes, pela ação antiproliferativa nos osteoblastos e indução da atividade dos osteoclastos Sibonga, 2001;Callaci et al, 2004). Suportando esta hipótese, foi demonstrado em camundongos submetidos à dieta hidroalcoólica a 26% durante 4 meses, que apesar destes animais não apresentarem alteração hepática e hormonal, tiveram uma redução significativa na densidade mineral óssea (DMO) e na quantidade e espessura de trabéculas ósseas, além da osteoclastogênese aumentada (Dai et al, 2000;Chakkalakal et al, 2005).…”
Section: Revisão De Literaturaunclassified
“…Além disso, estes animais apresentam afinidade para o consumo voluntário de solução alcoólica (Callaci et al, 2004;Chakkalakal et al, 2005;Rocha, 2005).…”
Section: Parâmetros Bioquímicosunclassified